Ion exchange fiber for hydrogen sulfide removal as well as preparation method and application of ion exchange fiber

By preparing an ion exchange fiber for hydrogen sulfide removal, the problems of thermally stable salt accumulation and low fiber utilization efficiency during the H2S removal process in the prior art are solved, and efficient and low-cost H2S removal and long-life use of fibers are achieved.

CN119633765AActive Publication Date: 2025-03-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311193751.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

The prior art has problems in the process of H2S removal in refinery gas, such as thermally stable salt accumulation, foaming of alcohol amine solution, reduction in extraction efficiency, and increased energy consumption and material consumption. The exchange capacity and utilization efficiency of ion exchange fibers are low, which limits its industrial application.

Method used

Polyacrylonitrile fibers, sodium hydroxide solution and alcohol substances are mixed in proportion, heated and stirred, then soaked and washed with organic acid solution, and further reacted with alcohol amine solution to prepare ion exchange fibers with high adsorption properties and long service life.

Benefits of technology

It realizes efficient removal of H2S in gases and liquids, reduces production costs and energy consumption, extends the service life of fibers, and realizes multiple reuses of fibers by controlling regeneration conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633765A_ABST
    Figure CN119633765A_ABST
Patent Text Reader

Abstract

The invention provides an ion exchange fiber for hydrogen sulfide removal and a preparation method and application thereof, the ion exchange fiber has the characteristics of low cost, good adsorption performance and long service life, can remove H2S in gas and liquid, and is wide in application range; meanwhile, by controlling the regeneration conditions of the ion exchange fibers, the ion exchange fibers can be repeatedly utilized for multiple times. The preparation method is simple in preparation process, easy to operate, good in repeatability and suitable for large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen sulfide removal, and particularly relates to an ion exchange fiber for hydrogen sulfide removal, a preparation method and an application thereof. Background Art

[0002] H2S (hydrogen sulfide) is an acutely toxic substance. Inhaling even small amounts of high concentrations can be fatal within a short period of time. Low concentrations can also affect the eyes, respiratory system, and central nervous system. H2S is soluble in water and readily soluble in alcohols, petroleum solvents, and crude oil. It is commonly found in industrial gases and waste gases such as refinery gas, natural gas, water gas, synthesis gas, and biogas. In chemical production processes, the presence of H2S can not only poison and deactivate catalysts but also cause severe corrosion of equipment and pipelines. Therefore, research on H2S removal technologies is of great significance.

[0003] In my country, amine-based desulfurization technology is commonly used to remove H2S from refinery gas. This involves reacting an alkylolamine solution (alkanolamine solution) with H2S and CO2 in the refinery gas to form the corresponding alkylolamine salt. This salt is then thermally decomposed to remove the H2S and CO2, thereby regenerating the alkylolamine solution. However, other acidic components in the system react with the amine to form heat-stable salts, which cannot be regenerated by thermal decomposition. During the recycling of the alkylamine solution, heat-stable salts accumulate, causing foaming of the alkylamine solution, reduced extraction efficiency, and entrainment of amine in the extraction product. This increases energy and material consumption during operation. In severe cases, this can lead to excessive sulfur content in liquefied gas and dry gas products, exacerbated equipment corrosion, and even corrosion and leakage.

[0004] Ion exchange fibers (IEFs) are a type of fibrous surface adsorption and separation material developed in recent years. They primarily rely on the exchange of exchangeable ions released by the dissociation of surfactant groups from the fibers or fibrous polymers with certain like-charge ions. Ion exchange fibers have a large surface area and a small diameter, and exhibit distinct kinetic properties, such as short migration distances, rapid adsorption rates, and high ion removal rates. They have broad application prospects in a variety of fields, including hazardous gas purification, heavy metal wastewater treatment, ultrapure water production, and seawater desalination. However, in actual applications, because the exchange capacity and product utilization efficiency of ion exchange fibers are lower than those of granular ion exchangers and powdered ion exchange materials, their industrial application is limited. Further reducing R&D and preparation costs and further improving product efficiency and service life are the development directions for ion exchange fibers.

[0005] CN1210763A discloses a method for manufacturing ion exchange fibers and its application. The ion exchange fibers are prepared using a swelling agent and a free radical protective agent. Since halides or aromatic compound swelling agents and chemical initiators are added during production, the production process becomes complicated and prone to pollution. Summary of the Invention

[0006] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide an ion exchange fiber for hydrogen sulfide removal, which has the characteristics of low cost, good adsorption performance and long service life. It can remove H2S from gases and liquids and has a wide range of applications. The present invention also provides a preparation method thereof, which has a simple preparation process, is easy to operate and has good repeatability, and is suitable for large-scale industrial applications.

[0007] To achieve the above object, according to one aspect of the present invention, a method for preparing an ion exchange fiber for removing hydrogen sulfide comprises the following steps: (1) Mixing polyacrylonitrile fiber, sodium hydroxide solution, and alcohol in proportion, reacting under heating and stirring conditions, soaking the polyacrylonitrile fiber after the reaction in an organic acid solution, washing it until it is neutral, and drying it to obtain a carboxyl-containing ion exchange fiber; (2) The carboxyl-containing ion exchange fiber obtained in step (1) is mixed with an alcoholamine solution in proportion, reacted under heating and stirring conditions, and the fibers after the reaction are washed to neutrality and dried to obtain the ion exchange fiber for hydrogen sulfide removal.

[0008] In some embodiments, in step (1), the alcohol substance includes one or more of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, and propylene glycol butyl ether.

[0009] In some embodiments, in step (1), the mass ratio of the polyacrylonitrile fiber, the sodium hydroxide solution and the alcohol substance is 1: (1-50): (1-80).

[0010] In some embodiments, in step (1), the organic acid includes one or more of methylbenzenesulfonic acid, p-methylbenzenesulfonic acid, oxalic acid, and formic acid; and the concentration of the organic acid is 0.01 wt%-10 wt%.

[0011] In some embodiments, in step (1), the reaction temperature is 40°C-100°C, and the reaction time is 0.1h-8h.

[0012] In some embodiments, in step (1), the drying temperature is 60°C-80°C, and the drying time is 5h-24h.

[0013] In some embodiments, in step (2), the alcoholamine is selected from one or more of N-(2-hydroxyethyl)ethylenediamine, ethanolamine, diethanolamine, isopropanolamine, and 1-amino-2-methyl-2-propanol.

[0014] In some embodiments, in step (2), the concentration of the alcoholamine solution is 1 wt%-30 wt%.

[0015] In some embodiments, in step (2), the mass ratio of the carboxyl-containing ion exchange fiber to the alcoholamine solution is 1:(10-100).

[0016] In some embodiments, in step (2), the reaction temperature is 60°C-140°C, and the reaction time is 0.5h-10h.

[0017] In some embodiments, in step (2), the drying temperature is 60°C-80°C, and the drying time is 0h-24h.

[0018] According to another aspect of the present invention, there is also provided an ion exchange fiber for removing hydrogen sulfide prepared according to the above method.

[0019] In some embodiments, the content of amine groups in the ion exchange fiber is 5 mmol / g-10 mmol / g, and the content of hydroxyl groups in the ion exchange fiber is 1 mmol / g-10 mmol / g.

[0020] According to another aspect of the present invention, the present invention also provides an application method of the above-mentioned ion exchange fiber for removing hydrogen sulfide, comprising the following steps: (1) The ion exchange fiber for hydrogen sulfide removal is loaded into a fixed bed reactor, wherein the reaction temperature of the fixed bed reactor is 20° C. to 60° C.; (2) The H2S-containing raw material is passed into a fixed bed reactor to remove the H2S.

[0021] In some embodiments, the application method further comprises the following step: when the ion exchange fibers in the fixed bed reactor reach adsorption saturation, regeneration liquid and water are introduced into the fixed bed reactor in sequence to regenerate the ion exchange fibers.

[0022] In some embodiments, the regeneration liquid includes one or more of sodium hydroxide solution, potassium hydroxide solution, and ammonia water; and the concentration of the regeneration liquid is 0.1 wt%-5 wt%.

[0023] In some embodiments, the regeneration conditions are: the feed rate of the regeneration liquid is 0.1 kg / h-8 kg / h, the feed time is 1-20 hours, and the regeneration temperature is 20°C-80°C.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The ion exchange fiber for hydrogen sulfide removal described in the present invention has the characteristics of low cost, good adsorption performance and long service life. It can remove H2S from gas and liquid and has a wide range of applications. At the same time, the present invention can realize multiple reuse of the ion exchange fiber by controlling the regeneration conditions of the ion exchange fiber.

[0025] (2) The method of the present invention firstly adjusts the fiber hydrolysis conditions, especially adds specific substances during the hydrolysis process, so as to control the reaction degree and prevent the fiber from dissolving due to violent reaction, so that a large number of carboxyl groups are generated after the raw fiber is hydrolyzed as anchor points for the grafted amino groups; at the same time, by adjusting the type of amino-containing substances and utilizing the charge effect of the groups, it is ensured that when the ion exchange fiber containing carboxyl groups reacts with the amino-containing substance, the reaction is more likely to proceed, thereby obtaining an ion exchange fiber containing both amino groups and hydroxyl groups.

[0026] (3) The preparation method of the present invention has a simple preparation process, is easy to operate and has good repeatability, and is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 This is a simplified diagram of the process for removing hydrogen sulfide in a fixed bed reactor.

[0028] The reference numerals in the figure are: 1-fixed bed reactor A, 2-fixed bed reactor B, 3-fixed bed reactor C. DETAILED DESCRIPTION

[0029] To facilitate understanding of the features and effects of the present invention by those skilled in the art, the following provides a general description and definition of the terms and expressions used in the specification and claims. Unless otherwise indicated, all technical and scientific terms used herein have the ordinary meanings as understood by those skilled in the art regarding the present invention. In the event of conflict, the definitions in this specification shall prevail.

[0030] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0031] Herein, when describing embodiments or examples, it should be understood that they are not intended to limit the present invention to these embodiments or examples. On the contrary, all alternatives, modifications and equivalents of the methods and materials described herein are encompassed within the scope defined by the claims.

[0032] In this document, for the sake of brevity, not all possible combinations of the various technical features in each embodiment or example are described. Therefore, as long as there are no contradictions in the combination of these technical features, the various technical features in each embodiment or example can be combined in any way, and all possible combinations should be considered to be within the scope of this specification.

[0033] The present invention provides a method for preparing ion exchange fibers for removing hydrogen sulfide, comprising the following steps: (1) Mixing polyacrylonitrile fiber, sodium hydroxide solution, and alcohol in proportion, reacting under heating and stirring conditions, soaking the polyacrylonitrile fiber after the reaction in an organic acid solution, washing it until it is neutral, and drying it to obtain a carboxyl-containing ion exchange fiber; (2) The carboxyl-containing ion exchange fiber obtained in step (1) is mixed with an alcoholamine solution in proportion, reacted under heating and stirring conditions, and the fibers after the reaction are washed to neutrality and dried to obtain the ion exchange fiber for hydrogen sulfide removal.

[0034] The present invention has no special limitation on the raw material polyacrylonitrile fiber, and conventional polyacrylonitrile fiber in the art can be used. For example, the linear density of the polyacrylonitrile fiber can be 1.5dtex-3dtex, and the length of the polyacrylonitrile fiber can be 35mm-50mm. Polyacrylonitrile fibers of different specifications have no obvious effect on the adsorption performance of the modified fiber.

[0035] According to the preparation method provided by the present invention, in step (1), the concentration of sodium hydroxide is 0.1wt%-50wt%. It can be understood that the concentration of sodium hydroxide can be any specific value of 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or any value within the range of 0.1wt%-50wt%.

[0036] According to the preparation method provided by the present invention, in step (1), the alcohol substance includes one or more of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, and propylene glycol butyl ether. The inventors have discovered that by adding specific types of alcohol substances during the hydrolysis of polyacrylonitrile, the degree of reaction can be better controlled, preventing a violent reaction from causing fiber dissolution.

[0037] According to the preparation method provided by the present invention, in step (1), the mass ratio of the polyacrylonitrile fiber, the sodium hydroxide solution and the alcohol substance is 1: (1-50): (1-80); preferably, the mass ratio is 1: (10-40): (10-60).

[0038] In the present invention, in step (1), the mass ratio of the polyacrylonitrile fiber, the sodium hydroxide solution and the alcohol substance is controlled within the above range. On the one hand, it can ensure that the cyanide groups in the polyacrylonitrile fiber are hydrolyzed under the action of base catalysis. On the other hand, it can control the degree of the hydrolysis reaction and prevent the polyacrylonitrile fiber from being excessively hydrolyzed.

[0039] According to the preparation method provided by the present invention, in step (1), the organic acid includes one or more of methylbenzenesulfonic acid, p-methylbenzenesulfonic acid, oxalic acid, and formic acid. In the present invention, the cyanide groups in the polyacrylonitrile fiber are hydrolyzed in the presence of sodium hydroxide to form sodium carboxylates. Soaking the polyacrylonitrile fiber in an organic acid solution can convert the sodium carboxylates into carboxyl groups. Furthermore, using an organic acid instead of an inorganic acid results in a milder reaction and less corrosion to the equipment.

[0040] Furthermore, the concentration of the organic acid is 0.01wt%-10wt%. It can be understood that the concentration of the organic acid can be any specific value of 0.01wt%, 0.1wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value within the range of 0.01wt%-10wt%.

[0041] According to the preparation method provided by the present invention, in step (1), the reaction temperature is 40°C-100°C. It is understandable that the reaction temperature can be any specific value among 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, and 100°C, or any value within the range of 40°C-100°C; the reaction time is 0.1h-8h. It is understandable that the reaction time can be any specific value among 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, and 8h, or any value within the range of 0.1h-8h.

[0042] According to the preparation method provided by the present invention, in step (1), the drying temperature is 60°C-80°C. It can be understood that the drying temperature can be any specific value among 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, and 80°C, or any value within the range of 60°C-80°C; the drying time is 5h-24h. It can be understood that the drying time can be any specific value among 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, and 24h, or any value within the range of 5h-24h.

[0043] According to the preparation method provided by the present invention, in step (2), the alcoholamine is selected from one or more of N-(2-hydroxyethyl)ethylenediamine (AEEA), ethanolamine (MEA), diethanolamine (DEA), isopropanolamine (MIPA), and 1-amino-2-methyl-2-propanol (AMP). In the present invention, small-molecule alcoholamines are selected for grafting modification. Compared with large-molecule amines, they have less steric hindrance and are easier to graft onto fibers. The resulting product has more uniform grafting and a better overall desulfurization effect. Uneven grafting can result in a good desulfurization effect in some parts and a poor desulfurization effect in others. At the same time, since the molecule contains both amino groups and hydroxyl groups, the reaction is easier to proceed, the grafting rate is higher, and the obtained product has a higher amino group content than small-molecule amines without hydroxyl groups.

[0044] Furthermore, the concentration of the alcoholamine solution is 1wt%-30wt%. It can be understood that the concentration of the alcoholamine solution can be any specific value of 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 72wt%, 28wt%, 29wt%, 30wt% or any value within the range of 1wt%-30wt%.

[0045] According to the preparation method provided by the present invention, in step (2), the mass ratio of the carboxyl-containing ion exchange fiber to the alcoholamine solution is 1:(10-100). It can be understood that the mass ratio of the carboxyl-containing ion exchange fiber to the alcoholamine solution can be any specific value of 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100 or any value within the range of 1:(10-100).

[0046] Furthermore, in step (2), the mass ratio of the carboxyl-containing ion exchange fiber to the alcoholamine solution is 1:(30-50).

[0047] According to the preparation method provided by the present invention, in step (2), the reaction temperature is 60°C-140°C. It is understandable that the reaction temperature can be any specific value among 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, and 140°C, or any value within the range of 60°C-140°C; the reaction time is 0.5h-10h. It is understandable that the reaction time can be any specific value among 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h, or any value within the range of 0.5h-10h.

[0048] According to the preparation method provided by the present invention, in step (2), the method of washing the reacted fiber to neutrality is not particularly limited, and conventional washing methods in the art can be used, including but not limited to washing with deionized water.

[0049] According to the preparation method provided by the present invention, in step (2), the drying temperature is 60°C-80°C. It can be understood that the drying temperature can be any specific value among 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, and 80°C, or any value within the range of 60°C-80°C; the drying time is 0-24h. It can be understood that the drying time can be any specific value among 0h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, and 24h, or any value within the range of 0-24h.

[0050] The present invention also provides an ion exchange fiber for removing hydrogen sulfide prepared according to the method.

[0051] In the present invention, the content of amino groups in the ion exchange fiber is 5mmol / g-10mmol / g. It can be understood that the content of amino groups can be any specific value among 5mmol / g, 6mmol / g, 7mmol / g, 8mmol / g, 9mmol / g, and 10mmol / g, or any value within the range of 5mmol / g-10mmol / g; the content of hydroxyl groups in the ion exchange fiber is 1mmol / g-10mmol / g. It can be understood that the content of hydroxyl groups can be any specific value among 1mmol / g, 2mmol / g, 3mmol / g, 4mmol / g, 5mmol / g, 6mmol / g, 7mmol / g, 8mmol / g, 9mmol / g, and 10mmol / g, or any value within the range of 1mmol / g-10mmol / g.

[0052] The inventors discovered that by adjusting the type of amino-containing substance and utilizing the charge effect of the group, the reaction between the ion exchange fiber containing carboxyl groups and the amino-containing substance is more likely to proceed, thereby obtaining an ion exchange fiber containing both amino groups and hydroxyl groups, and the amino group content in the product is higher.

[0053] When the ion exchange fiber of the present invention is used to remove hydrogen sulfide, hydrogen sulfide can react with the amine groups in the fiber, thereby achieving the removal of hydrogen sulfide in the raw material. The specific reaction is as follows: R x NH y H2O(s)→R x NH + y+1 (s)+OH - H2S+H2O→H3O + +HS - R x NH + y+1 (s)+HS - →R x NH y+2 S (s) The present invention also provides an application method of the ion exchange fiber for removing hydrogen sulfide, comprising the following steps: (1) The ion exchange fiber for hydrogen sulfide removal is loaded into a fixed bed reactor, wherein the reaction temperature of the fixed bed reactor is 20° C. to 60° C.; (2) The H2S-containing raw material is passed into a fixed bed reactor to remove the H2S.

[0054] In the present invention, before introducing the HS-containing feedstock for hydrogen sulfide removal, the ion exchange fibers may be treated with deionized water. For example, the deionized water treatment may be performed before or after the ion exchange fibers are loaded into the fixed-bed reactor. In the present invention, the water content of the ion exchange fibers after the deionized water treatment is 40 wt% to 50 wt%.

[0055] In the present invention, the fixed bed reactor can be a fixed bed reactor of a type commonly used in the art, and can include one or more reactors, for example, reactors A, B, and C. The ion exchange fiber loading conditions in the reactors can be completely consistent or inconsistent. The connection method between the multiple reactors is not limited and can be connected in series or in parallel. When the fixed bed reactor includes three reactors A, B, and C, the H2S-containing raw material can be fed from the bottom of the fixed bed reactors A, B, and C respectively, reacting with the amine-containing ion exchange fibers, and obtaining a purified material with H2S removed at the top of the tower. When the H2S content in the raw material is too high and a single reactor cannot meet the purification requirements, a secondary H2S removal can be performed by connecting the reactors in series, that is, the H2S-containing raw material is fed from the bottom of reactor A, the top product of reactor A is passed to the bottom of reactor B, and H2S removal is continued in reactor B to obtain a qualified product.

[0056] According to the application method provided by the present invention, the application method further includes the following steps: when the ion exchange fiber in the fixed bed reactor reaches adsorption saturation, regeneration liquid and water are successively introduced into the fixed bed reactor to regenerate the ion exchange fiber.

[0057] According to the application method provided by the present invention, the regeneration liquid includes one or more of sodium hydroxide solution, potassium hydroxide solution, and ammonia water.

[0058] According to the application method provided by the present invention, the concentration of the regeneration liquid is 0.1wt%-5wt%. It can be understood that the concentration of the regeneration liquid can be any specific value of 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or any value within the range of 0.1wt%-5wt%.

[0059] According to the application method provided by the present invention, the regeneration conditions are: the feed rate of the regeneration liquid is 0.1kg / h-8kg / h. It can be understood that the feed rate of the regeneration liquid can be any specific value of 0.1kg / h, 0.5kg / h, 1kg / h, 1.5kg / h, 2kg / h, 2.5kg / h, 3kg / h, 3.5kg / h, 4kg / h, 4.5kg / h, 5kg / h, 5.5kg / h, 6kg / h, 6.5kg / h, 7kg / h, 7.5kg / h, 8kg / h or any number within the range of 0.1kg / h-8kg / h. value; the feeding time of the regeneration liquid is 1h-20h. It can be understood that the feeding time can be any specific value among 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h or any value within the range of 1h-20h; the regeneration temperature is 20℃-80℃. It can be understood that the regeneration temperature can be any specific value among 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃ or any value within the range of 20℃-80℃.

[0060] The present invention adopts a process combining synthetic modified new materials with an adsorption fixed bed. By designing synthetic modified polyacrylonitrile fibers and optimizing the adsorption conditions of the fixed bed, H2S can be removed from both gas and liquid, and has a wide range of applications.

[0061] The present invention will be described in detail below by way of examples. It should be understood that the following examples are only used to further explain and illustrate the present invention, and are not intended to limit the present invention.

[0062] The chemical additives used in the examples and comparative examples of the present invention are all commercially available. The raw material polyacrylonitrile fiber is the fiber from Qilu Petrochemical Acrylic Fiber Plant, with a linear density of 1.67 dtex and a length of 38 mm.

[0063] The specific test standards and methods for various indicators in the present invention are as follows: Amine content detection: titration method is used for detection. The specific method is as follows: soak the fiber with excess 0.1mol / L hydrochloric acid solution to make the amine group + After sufficient reaction, add 0.1 mol / L sodium hydroxide solution until neutrality is reached, and calculate the amino group content.

[0064] Hydroxyl content detection: GB / T14074-2017 standard, iodine titration method is used to measure the hydroxyl content.

[0065] H2S content detection: ASTM D5623 standard, external standard method, using Agilent 8890 GC gas chromatograph equipped with Agilent 8355 dual plasma sulfur chemiluminescence detector (SCD) for detection.

[0066] Example 1 50g of polyacrylonitrile fiber, 100g of 10% sodium hydroxide solution, and 1000g of ethylene glycol methyl ether were reacted at 60°C for 5h, then soaked in 0.05% benzenesulfonic acid solution for 8h, washed until neutral, and dried at 60°C for 12h to obtain carboxyl-containing ion exchange fiber; 50g of carboxyl-containing ion exchange fiber, 2000g of 20% AEEA solution, 400g of 10% MEA and 600g of 15% AMP solution were added to a reactor and reacted at 120°C for 6h. The reacted fiber was then washed to neutrality and dried at 60°C for 1h to obtain ion exchange fiber IEF-1 for hydrogen sulfide removal.

[0067] After testing, the ion exchange fiber IEF-1 obtained in this example had an amino content of 7.2 mmol / g and a hydroxyl content of 4.5 mmol / g.

[0068] Example 2 50g of polyacrylonitrile fiber, 500g of 15% sodium hydroxide solution, and 500g of ethylene glycol ethyl ether were reacted at 40°C for 30min, then soaked in 1% p-toluenesulfonic acid solution for 3h, washed until neutral, and dried at 70°C for 20h to obtain carboxyl-containing ion exchange fiber; 50 g of carboxyl-containing ion exchange fiber and 1000 g of 5% AEEA solution were added to a reactor and reacted at 80°C for 10 h. The reacted fiber was then washed to neutrality and dried at 70°C for 10 h to obtain ion exchange fiber IEF-2 for hydrogen sulfide removal.

[0069] After testing, the ion exchange fiber IEF-2 obtained in this example had an amino content of 6.5 mmol / g and a hydroxyl content of 3.2 mmol / g.

[0070] Example 3 50g of polyacrylonitrile fiber, 1500g of 1% sodium hydroxide solution, and 300g of propylene glycol methyl ether were reacted at 80°C for 1h, then soaked in 2% oxalic acid solution for 1h, washed until neutral, and dried at 80°C for 15h to obtain carboxyl-containing ion exchange fiber; 50g of carboxyl-containing fiber, 2000g of 10% AEEA solution, 1000g of 5% MEA solution, 500g of 1% MIPA solution and 500g of 5% AMP solution were added to a reactor and reacted at 110°C for 8h. The reacted fiber was then washed to neutrality and dried at 70°C for 2h to obtain ion exchange fiber IEF-3 for hydrogen sulfide removal.

[0071] After testing, the ion exchange fiber IEF-3 obtained in this example had an amino content of 6.9 mmol / g and a hydroxyl content of 5.1 mmol / g.

[0072] Example 4 50g of polyacrylonitrile fiber, 800g of 30% sodium hydroxide solution, 1000g of ethylene glycol methyl ether, and 500g of ethylene glycol butyl ether were reacted at 70°C for 10min, then soaked in 0.5% formic acid solution for 2h, washed until neutral, and dried at 65°C for 24h to obtain carboxyl-containing ion exchange fiber; 50g of carboxyl-containing fiber, 1000g of 15% DEA solution and 500g of 30% AMP solution were added to a reactor and reacted at 100°C for 5h. The reacted fiber was then washed to neutrality and dried at 60°C for 8h to obtain ion exchange fiber IEF-4 for hydrogen sulfide removal.

[0073] After testing, the ion exchange fiber IEF-4 obtained in this example had an amino content of 5.7 mmol / g and a hydroxyl content of 6.5 mmol / g.

[0074] Example 5 50g of polyacrylonitrile fiber, 1000g of 25% sodium hydroxide solution, 1000g of ethylene glycol ethyl ether, 1000g of ethylene glycol butyl ether, and 1000g of propylene glycol methyl ether were reacted at 50°C for 4h, then soaked in 0.8% oxalic acid solution for 4h, washed until neutral, and dried at 75°C for 18h to obtain carboxyl-containing ion exchange fiber; 50g of carboxyl-containing fiber, 1000g of 20% MIPA solution and 1500g of 10% AMP solution were added to a reactor and reacted at 115°C for 7h. The reacted fiber was then washed to neutrality and dried at 65°C for 30min to obtain ion exchange fiber IEF-5 for hydrogen sulfide removal.

[0075] After testing, the ion exchange fiber IEF-5 obtained in this example had an amino content of 6.4 mmol / g and a hydroxyl content of 6.3 mmol / g.

[0076] Example 6 50g of polyacrylonitrile fiber, 2000g of 5% sodium hydroxide solution, 1000g of ethylene glycol ethyl ether, and 1500g of propylene glycol methyl ether were reacted at 65°C for 2h, then soaked in 0.3% formic acid solution for 5h, washed until neutral, and dried at 68°C for 10h to obtain carboxyl-containing ion exchange fiber; 50g of carboxyl-containing fiber, 1000g of 5% MEA solution and 1500g of 10% MIPA solution were added to a reactor and reacted at 90°C for 9h. The reacted fiber was then washed to neutrality and dried at 65°C for 3h to obtain ion exchange fiber IEF-6 for hydrogen sulfide removal.

[0077] After testing, the ion exchange fiber IEF-6 obtained in this example had an amino content of 6.1 mmol / g and a hydroxyl content of 5.9 mmol / g.

[0078] Application Example 1 The ion exchange fiber IEF-1 prepared in Example 1 was loaded into reactors A, B, and C in equal amounts. The inlet and outlet valves of reactors B and C were closed, and a raw material with an H2S content of 200 ppm was introduced from the bottom of reactor A. The reaction temperature was 30°C. After the raw material reacted with the ion exchange fiber in the reactor, the product was taken from the top of the tower. Analysis showed that the H2S content in the product was 0.2 ppm, and the H2S removal rate was 99.90%. After the ion exchange fibers in reactor A reached adsorption saturation, reactor B was used to remove H2S while reactor A was regenerated. Regeneration conditions were to first introduce 0.2% sodium hydroxide solution into reactor A at a rate of 0.5 kg / h for 5 hours, followed by deionized water at a rate of 1 kg / h for 10 hours, at a regeneration temperature of 30°C. After regeneration, reactor A was used again for H2S removal, under the same reaction conditions as before regeneration. Analysis showed that the H2S content in the overhead product after 10 regenerations was 0.5 ppm.

[0079] Application Example 2 The ion exchange fiber IEF-2 prepared in Example 2 was loaded into reactors A, B, and C in equal amounts. The inlet and outlet valves of reactors A and C were closed, and a raw material with an H2S content of 500 ppm was introduced from the bottom of reactor B. The reaction temperature was 50°C. After the raw material reacted with the ion exchange fiber in the reactor, a product was taken from the top of the tower. Analysis showed that the H2S content in the product was 0.6 ppm, and the H2S removal rate was 99.88%. After the ion exchange fibers in reactor B reached adsorption saturation, reactor C was used to remove H2S while reactor B was regenerated. Regeneration conditions were to first introduce 1% potassium hydroxide solution into reactor B at a rate of 1 kg / h for 2 hours, followed by deionized water at a rate of 5 kg / h for 5 hours, at a regeneration temperature of 20°C. After regeneration, reactor B was used again for H2S removal, under the same reaction conditions as before regeneration. Analysis showed that the H2S content in the product after six regenerations was 0.8 ppm.

[0080] Application Example 3 The ion exchange fiber IEF-3 prepared in Example 3 was loaded into reactors A, B, and C in equal amounts. The inlet and outlet valves of reactor C were closed, and a feedstock with an H2S content of 1000 ppm was introduced from the bottom of reactor A. After reacting with the ion exchange fiber, the feedstock was introduced into the bottom of reactor B. After secondary desulfurization, the product was collected from the top of reactor B. The reaction temperature of both reactors was 40°C. Analysis showed that the H2S content was 0.1 ppm, and the H2S removal rate was 99.99%. After the ion exchange fibers in reactor A reached adsorption saturation, reactors B and C were used as the first and second desulfurization reactors, respectively, while reactor A was regenerated simultaneously. Regeneration conditions were as follows: 0.3% sodium hydroxide solution was first introduced into reactor A at a rate of 0.3 kg / h for 6 hours, followed by deionized water at a rate of 6 kg / h for 15 hours. The regeneration temperature was 25°C. After regeneration was complete, reactors C and A were used as the first and second desulfurization reactors, respectively, while reactor B was regenerated simultaneously. The reaction and regeneration conditions were consistent with those previously described. Analysis showed that the H2S content in the product remained at 0.1 ppm after five regenerations.

[0081] Application Example 4 The ion exchange fiber IEF-4 prepared in Example 4 was loaded into reactors A, B, and C in equal amounts. The inlet and outlet valves of reactors B and C were closed, and a raw material with an H2S content of 100 ppm was introduced from the bottom of reactor A. The reaction temperature was 20°C. After the raw material reacted with the amino-group ion exchange fiber in the reactor, a product was withdrawn from the top of the tower. Analysis showed that the H2S content in the product was 0.9 ppm, and the H2S removal rate was 99.1%. After the ion exchange fibers in reactor A reached adsorption saturation, reactor B was used to remove H2S while reactor A was regenerated. Regeneration conditions were to first introduce 4% ammonia water into reactor A at a rate of 2 kg / h for 1 hour, followed by deionized water at a rate of 0.5 kg / h for 20 hours, at a regeneration temperature of 22°C. After regeneration, reactor A was used again for H2S removal, under the same reaction conditions as before regeneration. Analysis revealed a H2S content of 1.2 ppm in the product after three regenerations.

[0082] Application Example 5 The ion exchange fiber IEF-5 prepared in Example 5 was loaded into reactors A, B, and C in equal amounts. The inlet and outlet valves of reactors A and B were closed, and a raw material with an H2S content of 300 ppm was introduced from the bottom of reactor C. The reaction temperature was 35°C. After the raw material reacted with the amino-group ion exchange fiber in the reactor, the product was collected from the top of the tower. Analysis showed that the H2S content in the product was 0.2 ppm, and the H2S removal rate was 99.93%; After the ion exchange fibers in reactor C reached adsorption saturation, reactor A was used to remove H2S, while reactor C was simultaneously regenerated. Regeneration conditions were to first introduce 2% sodium hydroxide solution into reactor C at a rate of 0.6 kg / h for 8 hours, followed by deionized water at a rate of 4 kg / h for 12 hours, at a regeneration temperature of 45°C. After regeneration, reactor C was used again for H2S removal, using the same reaction conditions as before regeneration. Analysis revealed a H2S content of 1.5 ppm in the product after seven regenerations.

[0083] Application Example 6 The ion exchange fiber IEF-6 prepared in Example 6 was loaded into reactors A, B, and C in equal amounts. The inlet and outlet valves of reactor C were closed, and a feedstock with an H2S content of 800 ppm was introduced from the bottom of reactor A. After reacting with the amine-containing ion exchange fiber, the feedstock was introduced into the bottom of reactor B. After secondary desulfurization, the product was collected from the top of reactor B. The reaction temperature of both reactors was 45°C. Analysis showed that the H2S content was 0.4 ppm, and the H2S removal rate was 99.95%. After the ion exchange fibers in reactor A reached adsorption saturation, reactors B and C were used as the primary and secondary desulfurization reactors, respectively, while reactor A was regenerated simultaneously. Regeneration conditions were as follows: 0.8% potassium hydroxide solution was first introduced into reactor A at a rate of 1.2 kg / h for 3 hours, followed by deionized water at a rate of 2 kg / h for 6 hours, at a regeneration temperature of 38°C. Following regeneration, reactors C and A were used as the primary and secondary desulfurization reactors, respectively, while reactor B was regenerated simultaneously. The reaction and regeneration conditions were identical to those previously described. Analysis revealed a product H2S content of 1.4 ppm after eight regenerations.

[0084] Comparative Example 1 50g of polyacrylonitrile fiber was reacted with 1000g of 25% sodium hydroxide solution at 50°C for 4h. The experiment found that the ion exchange fiber gradually dissolved under these conditions, and only a small amount of solid fiber was finally obtained.

[0085] Comparative Example 2 A feedstock with a hydrogen sulfide content of 400 ppm is introduced from the bottom of the desulfurization reactor, while a 30% MEA solution is introduced from the top. The two react in a countercurrent fashion in the desulfurization reactor to remove hydrogen sulfide. The reaction temperature is 30°C. The MEA solution, which has absorbed hydrogen sulfide, enters the regeneration system from the bottom of the desulfurization reactor and, after regeneration, returns to the desulfurization reactor for recycling. The hydrogen sulfide concentration in the product is initially 0.9 ppm. Over time, liquid entrainment gradually occurs in the product, and the hydrogen sulfide concentration in the product increases. After 200 hours of operation, the hydrogen sulfide content in the product reaches 38 ppm.

[0086] Comparative Example 3 50g of polyacrylonitrile fiber, 500g of 15% sodium hydroxide solution, and 500g of ethylene glycol ethyl ether were reacted at 40°C for 30min, then soaked in 1% p-toluenesulfonic acid solution for 3h, washed until neutral, and dried at 70°C for 20h to obtain carboxyl-containing ion exchange fiber; 50g of carboxyl-containing fiber and 1000g of 5% triethylenetetramine solution were added to a reactor and reacted at 80°C for 10h. The reacted fiber was then washed to neutrality and dried at 70°C for 10h to obtain ion exchange fiber containing amino groups.

[0087] After testing, the content of amino groups in the ion exchange fiber obtained in this comparative example was 4 mmol / g, and no hydroxyl groups were detected.

[0088] The ion exchange fiber of Comparative Example 3 was loaded into reactor A, reactor B, and reactor C in equal amounts. The inlet and outlet valves of reactors B and C were closed, and a raw material with an H2S content of 200 ppm was introduced from the bottom of reactor A. The reaction temperature was 30°C. After the raw material reacted with the ion exchange fiber in the reactor, the product was taken from the top of the tower. Analysis showed that the H2S content in the product was 14.6 ppm, and the H2S removal rate was 92.7%.

[0089] As can be seen, the ion exchange fiber prepared according to the method described in the embodiment of the present invention has abundant amino and hydroxyl groups. The ion exchange fiber has good adsorption performance, with a hydrogen sulfide removal rate of over 99%. Comparison 3 shows that when a hydroxyl-free amine is reacted with a carboxyl-containing fiber, the amino group content in the product fiber is relatively low, and therefore the hydrogen sulfide removal rate is only 92.7%, which is far inferior to the effect of the embodiment of the present application. At the same time, by controlling the regeneration conditions of the ion exchange fiber, the present invention can achieve multiple reuse of the ion exchange fiber.

[0090] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing ion exchange fibers for removing hydrogen sulfide, characterized in that: The steps include: (1) polyacrylonitrile fiber, sodium hydroxide solution and alcohol are mixed in proportion, reacted under heating and stirring conditions, and the polyacrylonitrile fiber after the reaction is soaked in an organic acid solution, washed until neutral, and dried to obtain carboxyl-containing ion exchange fiber; (2) The carboxyl-containing ion exchange fiber obtained in step (1) is mixed with an alcoholamine solution in proportion, reacted under heating and stirring conditions, and the fibers after the reaction are washed to neutrality and dried to obtain the ion exchange fiber for removing hydrogen sulfide.

2. The method for preparing ion exchange fibers for removing hydrogen sulfide according to claim 1, characterized in that: In step (1), the alcohol substance includes one or more of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, and propylene glycol butyl ether.

3. The method for preparing ion exchange fibers for removing hydrogen sulfide according to claim 1, characterized in that: In step (1), the mass ratio of the polyacrylonitrile fiber, the sodium hydroxide solution and the alcohol substance is 1:(1-50):(1-80).

4. The method for preparing ion exchange fibers for removing hydrogen sulfide according to claim 1, characterized in that: In step (1), the organic acid includes one or more of toluenesulfonic acid, p-toluenesulfonic acid, oxalic acid, and formic acid; and the concentration of the organic acid is 0.01wt%-10wt%.

5. The method for preparing ion exchange fibers for removing hydrogen sulfide according to claim 1, characterized in that: The method has one or more of the following features: In step (2), the alcoholamine is selected from one or more of N-(2-hydroxyethyl)ethylenediamine, ethanolamine, diethanolamine, isopropanolamine, and 1-amino-2-methyl-2-propanol; In step (2), the concentration of the alcoholamine solution is 1wt%-30wt%.

6. The method for preparing ion exchange fibers for removing hydrogen sulfide according to claim 1, characterized in that: In step (2), the mass ratio of the carboxyl-containing ion exchange fiber to the alcoholamine solution is 1:(10-100).

7. An ion exchange fiber for hydrogen sulfide removal prepared according to the preparation method according to any one of claims 1 to 6, characterized in that: The content of amine groups in the ion exchange fiber is 5 mmol / g-10 mmol / g, and the content of hydroxyl groups in the ion exchange fiber is 1 mmol / g-10 mmol / g.

8. A method for using the ion exchange fiber according to claim 7, characterized in that: The steps include: (1) The ion exchange fiber is loaded into a fixed bed reactor, wherein the reaction temperature of the fixed bed reactor is 20° C. to 60° C.; (2) The H2S-containing raw material is passed into a fixed bed reactor to remove the H2S.

9. The application method according to claim 8, characterized in that: The method also includes the following steps: when the ion exchange fibers in the fixed bed reactor reach adsorption saturation, regeneration liquid and water are introduced into the fixed bed reactor in sequence to regenerate the ion exchange fibers.

10. The application method according to claim 8, characterized in that: The regeneration liquid includes one or more of sodium hydroxide solution, potassium hydroxide solution, and ammonia water; the concentration of the regeneration liquid is 0.1wt%-5wt%.

Citation Information

Patent Citations

  • Method for preparing amphoteric antibacterial ion exchange fibers

    CN106049054A

  • Preparation method and using method for polyamino / amidoxim-modified multifunctional ion exchange fibers

    CN109289803A

  • Preparation method of solid amine fiber cloth with high amino content

    CN114011385A

  • Method for preparing polyacrylonitrile fiber adsorbent and adsorbent thereof

    KR1020160113374A

  • Fiber sorbents

    US20100313755A1